Desafios do modo de vida da pesca artesanal em água doce num contexto socioambiental adverso : uma análise sociológica do caso do bairro rural do Tanquã, Piracicaba/SP - Venturato, Raquel Duarte (2008)
The intensification concerning the multiple uses of water in the Piracicaba River Basin has led to alterations in the aquatic ecosystem, affecting the fishery supplies with a deleterious influence and causing great limitations to the survival and social reproduction of traditional communities. The way of life within Tanquã community is centered on the artisan fishery, which implies on the fabrication of their own corporal techniques, ways of production, knowledge, beliefs and habits all characterized as traditional. The deterioration of the aquatic ecosystem acts as a factor of dissolution in this way of life. On one hand, by compromising and restricting the use of natural resources and on the other hand, by demanding the modernization of such techniques so that the artisan fishery can gain additional life span. There is reluctance within the Tanquã that appears as representations of their universe, in the oral memory, and the extra-economic sociability, providing a counterview to a full commitment to the market rationality. Between the desire to resist, affirming itself as a valid way of life, and the need to adjust to the dynamics of macro social environments, the Tanquã community lives the duality of a collective identity, sometimes strengthen, and sometimes threatened. As a case study, the objective of this article presents a brief description and a sociological analysis of the process, from a qualitative approach, in which the oral account and the direct observation are blend to characterize the structure and the dynamics of social production of the community.